“Desire Is Like a Dreadful Monster”: Analysis of Extended Metaphors in L2 Argumentative Essays by Chinese Learners of English - Lu, Qiuyun (Frontiers in Psychology, 2021)
This article explores the use, function and understanding of extended metaphors in L2 argumentative essays by Chinese learners of English. The analysis starts with the identification of linguistic metaphors and extended metaphors in 72 argumentative texts produced by 37 intermediate Chinese English majors. Halliday and Matthiessen’s (2004) framework of the three meta-functions of language and Hyland’s (1990) model of the rhetorical structure of an L2 argumentative essay are applied to the analysis of functions of extended metaphors, with adopting the bottom-up approach of establishing systematic metaphors from identified extended metaphors to draw inferences about learners’ communicative intentions in producing extended metaphors. To understand learners’ thinking processes behind using extended metaphors while writing, I interviewed 4 of 11 writers about the process of writing extended metaphors in their texts in the stimulated recall interviews. I find that extended metaphors, expressed through similes or direct metaphors at strategic stages in L2 argumentative essays, are often the result of learners’ conscious manipulation of L1 in producing L2 for various communicative purposes, such as desire for vividness, coherence, comprehensibility when there is a knowledge gap between L1 and L2, and for evaluative and persuasive power. These communicative functions are consistent with the ideational, interpersonal, and textual functions of language, which also coincides and interacts with the rhetorical goals of moves and stages in L2 argumentative essays. Metaphoric thinking, L1 influence and struggling to express meaning and persuade, cited in learners’ thought reports, are major factors triggering extended metaphors. Findings of this article can contribute to the knowledge of learners’ metaphoric competence in L2, which can in turn enrich teachers’ metaphor knowledge and draw teachers’ attention to learners’ creative ways of using metaphors and then raising metaphor awareness in L2 writing teaching and learning.